THE TRANS-AFGHAN TRANSPORT CORRIDOR: STATE INTERESTS AND DEVELOPMENT PROSPECTS - ZOKHIDOV, Azamat (CENTRAL ASIA AND THE CAUCASUS, 2012)
Efforts are currently being stepped up to create a Trans-Afghan transport corridor (TATC), motivated primarily by its vast transit capabilities and the role it can play in developing economic relations in the Central Asia region. Furthermore, it is important to note that building a transport infrastructure in Afghanistan capable of invigorating integration with neighboring states is not only vital for developing the country’s economy, but also for ensuring its domestic political stability.Given their unique geographic location, Uzbekistan and Afghanistan have advantageous conditions for creating and developing intercontinental transport corridors. For example, the main international transport corridors pass through the territory of Uzbekistan, which is one of the largest Central Asian states. This makes it extremely attractive from the viewpoint of Eurasian goods and passenger transit via the shortest route in essentially all directions. Moreover, intensive development of Uzbekistan’s foreign trade demands organizing efficient international cargo carriage.On 18 June 2003, in order to promote the restoration of Afghanistan’s economy, raise its transit potential, and develop economic trade co-operation in the region, the heads of state of Uzbekistan, Afghanistan, and Iran signed an Agreement on building international transport corridors via the Termez-Hayraton-Mazar-e Sharif-Herat-Meshed-Bandar Abbas route. It should be noted that full-fledged implementation of this project largely depends on how all-embracing and simi-lar the interests of the regional states are, as well as on the level of their cooperation in this vector.This article analyzes the interests of those states involved in creating the TATC, as well as the prospects for its development.